Meta-analysis reveals that grain quality is improved in ratoon season crop compared with main crop - Yang, Xuelian; Ruan, Zhijie; Chen, Kezhi; Gu, Shiting; Wang, Yuchao; Cai, Qiang; Yao, Li-Ang; Boorboori, Mohammad Reza; Yasir, Arafat; Chaiwanon, Juthamas; Bessho-Uehara, Kanako; Shin, Kihye; et al. (Frontiers in Plant Science, 2025)
Rice ratooning cultivation refers to secondary production from the stubble left after the harvest of the main crop (MC). Besides providing additional yield, ratooning is known to affect grain quality. Here, we conducted a meta-analysis of grain quality traits between ratoon season crop (RC) and MC. The results showed that the overall grain quality of RC was higher than that of MC. Ratooning improved milling traits by increasing the milled rice rate (MRR) and head rice rate (HRR) and enhanced grain appearance by reducing chalkiness. Furthermore, ratooning had a positive impact on alkali spreading value (ASV) and amylose content (AC) but a negative influence on gel consistency (GC), which markedly affects cooking and sensory quality. Subgroup analysis showed that stubble height influenced the AC of RC, while planting region was a major factor regulating most grain properties. Meta-regression analysis suggested that latitude, precipitation, and temperature played important roles in rice quality, particularly in relation to milling parameters. In addition, we compared the grain quality of RC and the late-season crop (LC) with synchronized heading time. Negative trends were observed in brown rice rate (BRR) and protein content (PC), while planting region and rice variety were revealed as factors influencing chalkiness and HRR. Overall, our findings indicate that ratooning has positive impacts on grain quality and uncover the relationships between environmental and agronomic factors and their effects on quality traits, which will lay the foundation for future breeding strategies and optimize cultivation management across growth regions.